Effects of nitrogen application on winter wheat growth, water use, and yield under different shallow groundwater depths - She, Yingjun; Li, Ping; Qi, Xuebin; Rahman, Shafeeq Ur; Guo, Wei (Frontiers in Plant Science, 2023)
Shallow groundwater plays a vital role in physiology morphological attributes, water use, and yield production of winter wheat, but little is known of its interaction with nitrogen (N) application. Our aim is to explore the effects of N fertilization rate and shallow groundwater table depth (WTD) on winter wheat growth attributes, yield, and water use. Experiments were carried out in micro-lysimeters at WTD of 0.6, 0.9, 1.2, and 1.5 m with 0, 150, 240, and 300 kg/ha N application levels for the winter wheat (Triticum aestivum L.). Results showed there was an optimum groundwater table depth (Op-wtd), which the growth attributes, groundwater consumption (GC), yield, and water use efficiency (WUE) under each N application rate were maximum, and the Op-wtd decreased with the N application increase. The Op-wtd corresponding to the higher velocity of groundwater consumption (Gv) appeared at the late jointing stage, which was significantly higher than other WTD treatments under the same N fertilization. WTD significantly affected the Gv during the seeding to the regreening stage and maturity stage; the interaction of N application, WTD, and N application was significant from the jointing to filling stage. The GC, leaf area index (LAI), and yield increased with increase of N application at 0.6-0.9 m depth; such as the yield and WUE of the NF300 treatment with 0.6 m depth were significantly higher than those of the NF150-NF240 treatment, 20.51% and 14.81%, respectively. At 1.2-1.5 m depth, the N application amount exceeding 150-240 kg/ha were not conducive to wheat growth, groundwater use, grain yield, and WUE; these indexes were better under the N application of 150 kg/ha, which the yield and WUE of 150 kg/ha treatment were 15.02% and 10.67% higher than those of 240-300 kg/ha treatment at 1.2 depth significantly. The optimum N application rate corresponding to yield indicated a tendency to decrease with the WTD increase. Considering the winter wheat growth attributes, GC, yield, and WUE, 150-240 kg/ha N application was recommended in our experiment. It can be concluded that interaction exists obviously between nitrogen fertilizer and shallow groundwater, which affects crop water and nitrogen utilization.